Automation for fire insurance of Talasco Insurance Sdn. Bhd. / Mohd Yusof Maeraj ... [et al.] - Maeraj, Mohd Yusof; Wan Ahmad, Wan Zanariah; Abdullah, Norliza; Sheriff, Rooszita (1990)
Data plays an important role in our work enviroment. If data is efficiently handled, work can proceed smoothly and effectively. Dbase III plus is computer programme to handle data. It is an especially powerful and flexible system for storing, organising and retrieving information on a microcomputer.